Crossbred progeny production performance under rural areas of Eastern Uttar Pradesh - R L Bhagat; Brajesh Kumar; Bansh Narayan; Raviraj Jadhav; N L Phadke; AB Pande (Journal of Livestock Biodiversity, 2025)
The field progeny-testing program of Holstein Friesian crossbred bulls sponsored by National Dairy Plan phase-I is operated in districts of Eastern Uttar Pradesh. The scheme was coordinated through National Dairy Development Board (NDDB), Anand, Gujarat, in India. Total 649 crossbred progeny (Holstein Friesian x Local) owned by 629 farmers spread over seventy cattle Development centres from Azamgarh, Gorakhpur, Jaunpur and Sultanpur district of Eastern Uttar Pradesh were reached to age at first calving (AFC) and completed their 1st lactation. The production performance of progeny was studied based on districts (4), sire (20), birth year (2), season of calving (3) and age at first calving (AFC) months (5 groups). The 305 days milk yield was computed from the monthly milk yield records of morning and evening milking. The first milk recording got within fifteen days after calving and incomplete milk recording due to sale, transfer or death of progeny were excluded from study. The average first lactation 305 days milk yield of crossbred progeny under field conditions of Eastern Uttar Pradesh was recorded as 2461.99±232.88 kg and it was significantly affected due to districts, birth year, calving season and AFC months at field conditions.